As interfaces do reprocessamento de endoscópios pelo uso de glutaraldéido em serviços de endoscopia de Goiânia - BARBOSA, Jackeline Maciel (2008)
SUMMARY: This is a descriptive research carried out in twenty digestive endoscopy services at the municipality of Goiânia. We aimed at characterizing the endoscope reprocessing through the use of glutaraldeide in upper digestive endoscopy services. The sample was constituted by endoscopes used for upper digestive endoscopy and professionals performing these endoscope reprocessing. We observed ethical legal aspects of human research. Data was collected through direct observation of the physical structure of the place used for endoscope reprocessing and the individuals performing such reprocessing and recorded in a check list. In each service we obtained samples of three endoscopes, able to be chosen the first, the second, and the last endoscope used in that period. Samples were collected in the border, biopsy channel, and aspiration channel of each endoscope right after the use and at the end of reprocessing. Samples were processed in the Laboratório de Bacteriologia Médica of the Instituto de Patologia Tropical e Saúde Pública of the Universidade Federal de Goiás. Microorganisms were identified concerning the form through Gram coloring technique. For isolated bacteria we performed the susceptibility profile. We carried out twenty observations regarding physical structure, one in each service. Sixty endoscope reprocessing were observed, three in each service. The outcomes showed that reprocessing is carried out in the same screening room without proper flow of service. All reprocessing stages showed failure. Errors were observed during the cleansing stage due to the use of enzyme detergent and brushing only the biopsy tubes. Disinfection was identified in all reprocessing, however it was not observed at 2 % concentration of germicide, there was no aspiration of the product in the internal channels and total immersion of the endoscopes, and exposure time to glutaraldeide was lower than the recommended one. Rinsing was most of the time with unfiltered water. The internal channels drying was improper due to the nonuse of compressed air. Adequate conditions to endoscope storage were identified. Microbial range of contaminated endoscopes was low, between 101 a 104 ufc/mL. Performing the precleansing stage, the use of enzyme detergent, cleansing of internal endoscope tubes, and the filling of these tubes with glutaraldeide were the significant variables, < 0.005 for the efficiency of endoscope reprocessing. These stages were crucial to reduce microbial burden. Chemical disinfection through the use of glutaraldeide was efficient in the endoscope reprocessing in eight services which is evidenced through the elimination of initial microbial range, however failures in the reprocessing of those were identified. We isolated from decontaminated endoscope: S. aureus, Staphylococcus coagulase negative, Enterobacter agglomerans, Enterobacter sp., E. coli. These microorganisms were susceptible to antimicrobials tested, except for azitromycin-resistant Gram-negative bacteria. This study shows that despite the low microbial range of contaminated endoscopes, disinfection has not been achieved in all services due to reprocessing failures, mainly in the cleaning stage. We consider adherence to endoscopes reprocessing protocols eliminates the major failures identified in the reprocessing